The first Protestant missionaries and the modernization of Korea - Park, Dong-Kweon ([n.p.] : South East Asia Graduate School of Theology, 1993)
There were two great changes in the spiritual history of Korea in modern times.
The first came in the 14th century when the Chosun dynasty ruled by the Yi family succeeded to the Koryo dynasty, and replaced Buddhism with Confucianism as the state cult. The second came with the opening of Korea to international trade and relations in the late 19th century toward the end of the Chosun dynasty. But this time, Confucianism had proved incapable of giving the answer to the spiritual search of the Korean people, in the midst of pressures arising from changing political and economic conditions and the challenge of modernization.
In partial fulfillment of the requirements for the degree of Master of Theology (S.E.A.)
A thesis presented to the faculty of the South East Asia Graduate School of Theology
Thesis (M. Theo.)- South East Asia